Ømålsordbogen mellem synkroni og diakroni - Hovmark, Henrik (LexicoNordica, 2006)
The Danish Dictionary of the Insular Dialects covers a period from 1750 to 1945, 1850– 1920 being its core period. As such it can clearly be labelled an historical dictionary. But at the outset, during the first decades of the 20th century, the intention was to make a contemporary synchronic dictionary. However, constant delays of the editing process (vol. 1 appeared only in 1992) soon made the original plans of a contemporary dictionary impossible. Furthermore, the synchronic ideal was challenged by the fact that the time span under consideration was expanded both backwards and forwards. Thus, traits of diachrony and historical perspective have been introduced into a dictionary that in principle is still trying to fulfil its original synchronic ideal.